Β2‐adrenergic stimulation potentiates spontaneous calcium release by increasing signal mass and co‐activation of ryanodine receptor clusters. (6th November 2021) - Nolla‐Colomer, Carme; Casabella‐Ramon, Sergi; Jimenez‐Sabado, Veronica; Vallmitjana, Alexander; Tarifa, Carmen; Herraiz‐Martínez, Adela; Llach, Anna; Tauron, Manel; Montiel, Jose; Cinca, Juan; Chen, S. R. Wayne; Benitez, Raul; et al.
Abstract: Aims: It is unknown how β‐adrenergic stimulation affects calcium dynamics in individual RyR2 clusters and leads to the induction of spontaneous calcium waves. To address this, we analysed spontaneous calcium release events in green fluorescent protein (GFP)‐tagged RyR2 clusters. Methods: Cardiomyocytes from mice with GFP‐tagged RyR2 or human right atrial tissue were subjected to immunofluorescent labelling or confocal calcium imaging. Results: Spontaneous calcium release from single RyR2 clusters induced 91.4% ± 2.0% of all calcium sparks while 8.0% ± 1.6% were caused by release from two neighbouring clusters. Sparks with two RyR2 clusters had 40% bigger amplitude, were 26% wider, and lasted 35% longer at half maximum. Consequently, the spark mass was larger in two‐ than one‐cluster sparks with a median and interquartile range for the cumulative distribution of 15.7 ± 20.1 vs 7.6 ± 5.7 a.u. ( P  < .01). β2‐adrenergic stimulation increased RyR2 phosphorylation at s2809 and s2815, tripled the fraction of two‐ and three‐cluster sparks, and significantly increased the spark mass. Interestingly, the amplitude and mass of the calcium released from a RyR2 cluster were proportional to the SR calcium load, but the firing rate was not. The spark mass was also higher in 33 patients with atrial fibrillation than in 36 without (22.9 ± 23.4 a.u. vs 10.7 ± 10.9; P  = .015). Conclusions: Most sparks are caused by activation of a single RyR2 cluster at baseline while β‐adrenergic stimulation doubles the mass and the number of clusters per spark. This mimics the shift in the cumulative spark mass distribution observed in myocytes from patients with atrial fibrillation.